Návrh upínacího přípravku pro měření tření a opotřebení v recipročním modulu tribometru - Zeman, Petr (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Tato práce řeší návrh upínacího přípravku pro upínaní plošných vzorků do recipročního modulu tribometru. Upínač je konstruován pro kompenzaci tvarových odchylek vzorků naklápěním ve dvou osách v malém rozsahu. Cíl byl naplněn, mechanismus naklápění je vyřešen rotací kulové plochy. Přípravek je dostatečně tuhý a bylo dosaženo lepší ovladatelnosti a opakovatelnosti upnutí. Práce obsahuje přehled komerčně dostupných metod upnutí, jejich zhodnocení a popis konstrukce vlastního přípravku, který zjednodušuje upnutí rozdílně velkých vzorků do recipročního modulu tribometru UMT TriboLab.

The thesis deals with design of a clamping fixture for fastening surface samples for the reciprocating drive of the tribometer. The fixture is designed to compensate for shape deviations of the samples by tilting in two axes in a small range. The objective has been fulfilled, the tilting mechanism is achieved by rotating the spherical surface. The fixture is sufficiently rigid. It has been achieved of better user experience and repeatability of clamping. The paper contains an overview of commercially available clamping methods, their evaluation and description of the construction of the newly designed device, which simplifies the clamping of uniquely shaped samples for the reciprocating drive of the UMT TriboLab tribometer.
Design of reciprocal module fixture for wear and friction measurements in tribometer
Keywords: naklápěcí upínač; tribometr; reciproční modul; návrh přípravku; tilting fixture; tribometer; reciprocating drive; design of fixture